RESULTS OF MONITORING THE SETTLEMENT OF SILO FOUNDATIONS REINFORCED WITH SOIL-CEMENT ELEMENTS - Butenko, A.; Mozhovyi, A. (Municipal economy of cities. Series: «Economy science», 2024)
During the first cycle of loading and in the subsequent process of steel silos operation to store grain, special attention goes to the observation of base settlement under silo foundations and their tilting. Traditionally, silo settlement tends to be monitored by geodetic measurements. To analyse the results of monitoring for the silos base settlement, we used the linearity changing of the base stiffness approach. The base stiffness is the ratio of the average pressure p (in kPa) under the foundation sole to the average settlement S (in mm). This approach relies on the following assumption: in the process of silo loading, thus gradually increasing the average pressure under the sole of the foundation, the modulus of deformation of the base soil gradually decreases, and the deformability of the base increases until the stresses in the soil mass under the foundation do not exceed the values of the calculated resistance and the development of plastic deformations begins. For grain storage elevator silos 10.1–10.12 located in the Khmelnytskyi region, we obtained the ratio of the average pressure p (in kPa) under the foundation sole to the average settlement S (in mm) during the geodetic monitoring, and then, we used it to construct the stiffness graphs of the silo base. The base stiffness indicators of silos 10.2 and 10.3 most closely match the calculated base stiffness. The specified values of base stiffness exceeding the measured ones by 3–5% are probably due to the higher calculated mechanical characteristics of the base reinforced with soil-cement elements. The rigidity of the silo base and the average pressure in the base under the foundations calculated based on geodetic measurement data are independent random variables, as evidenced by the graphs of the rigidity of the silo base 10.1–10.12. The study of the correlation between the specified random variables is of practical interest. The obtained value of the sample correlation coefficient r = –0.4687 indicates a negative correlation between the samples of the average pressure p (in kPa) under the foundation sole and the stiffness of the base (p / S, kPa/mm). The existence of negative correlation dependence has a clear physical meaning, such as when the pressure on the base increases, its stiffness decreases while increasing the deformability of the base, as confirmed by the results of silo geodetic monitoring. The calculated stiffness of the base decreases with increasing pressure due to the involvement of a greater depth of the compressible stratum, and, accordingly, the calculated deformability of the base increases. To determine the physical and mechanical properties of the base soil, the generally accepted pressure range during the tests does not exceed 250 kPa. A priori, this pressure range corresponds to the elastic section of the soil deformation diagram and the gradual decrease in mechanical characteristics. The average stresses under the foundations of the studied silos did not exceed 125 kPa. Therefore, the proposed method makes it possible to obtain not only quantitative conclusions – the magnitude of base settlement, but also to analyse qualitative indicators related to the stiffness characteristics (р / S, kPa/mm) of the base and to assess its deformation indicators acceptability.